Kebijakan penanganan stunting pada anak usia 24-59 bulan: A scoping review - Ahmad, Nurul Fauziah; Nugraheni, Sri Achadi; Winarni, Sri (Holistik Jurnal Kesehatan, 2025)
Background: Stunting is a condition where a child is physically too short for their age, which can cause problems for both their physical and cognitive abilities in the future. Stunting is known to be caused not only by the characteristics of the toddler but also by various factors, even beyond health, making stunting management policies crucial in overcoming stunting. Purpose: To map policies for managing stunting in children aged 24-59 months. Method: A scoping review was conducted using literature searches in the Science Direct and PubMed Central databases using the keywords "stunting AND policy OR treatment OR intervention OR reduction OR governance program OR policy report OR policy research AND children aged 24-59 months," resulting in 7,567 articles. These articles were then screened, resulting in nine articles that truly met the research objectives. Results: Policymakers in various countries have implemented a variety of stunting management policies, ranging from improving toddler diets, exclusive breastfeeding campaigns, improving maternal factors, improving health services, improving access to nutrition, to related agricultural policies, food security, and poverty alleviation. Conclusion: The incidence of stunting in toddlers in various countries is influenced by various factors, not just health, so its management requires support from various sectors. Stunting can be caused by the characteristics of the toddlers themselves, so treatment can include providing complementary feeding or improving the diet of children aged 6-23 months, as well as providing micronutrient powder containing iron. Furthermore, it is necessary to control maternal characteristics, such as the mother's age at marriage, the mother's education, and the mother's BMI during pregnancy.   Keywords: Policy; Stunting Management; Toddlers Aged 24-59 Months.   Pendahuluan: Stunting adalah kondisi ketika anak secara fisik terlalu pendek dibandingkan usianya yang dapat menimbulkan masalah baik bagi fisik itu sendiri maupun kemampuan kognitifnya di masa yang akan datang. Stunting diketahui tidak hanya disebabkan oleh karakteristik balita itu sendiri, melainkan juga dipengaruhi oleh berbagai faktor yang bahkan diluar kesehatan, sehingga kebijakan penanggulangan stunting menjadi penting dalam mengatasi stunting. Tujuan: Untuk memetakan kebijakan penanganan stunting pada anak usia 24-59 bulan. Metode: Penelitian scoping review dengan penelusuran literatur pada database Science Direct dan PubMed Central menggunakan kata kunci “stunting AND policy OR treatment OR intervention OR reduction OR governance program OR policy report OR policy research AND children age 24-59 months” yang menghasilkan 7,567 artikel. Selanjutnya dilakukan seleksi terhadap artikel-artikel tersebut, sehingga ditemukan 9 artikel yang benar-benar sesuai dengan tujuan penelitian. Hasil: Para pemangku kebijakan dari berbagai negara telah menerapkan berbagai macam kebijakan penanganan stunting, mulai dari perbaikan pola makan balita, kampanye pemberian ASI eksklusif, peningkatan faktor maternal ibu, perbaikan layanan kesehatan, perbaikan akses terhadap gizi, hingga kebijakan terkait pertanian, ketahanan pangan, dan pengentasan kemiskinan. Simpulan: Kejadian stunting pada balita di berbagai negara dipengaruhi oleh berbagai faktor, tidak hanya kesehatan, sehingga dalam penanganannya juga memerlukan dukungan dari berbagai sektor. Stunting dapat disebabkan oleh karateristik balita itu sendiri, maka penanganannya dapat dilakukan melalui pemberian MP-ASI atau peningkatan pola makan pada anak usia 6-23 bulan hingga pemberian bubuk mikronutrien yang mengandung zat besi. Disamping itu, diperlukan pula pengendalian bagi karakteristik ibu, seperti usia ibu ketika menikah, pendidikan ibu, hingga BMI ibu ketika hamil.   Kata Kunci: Balita Usia 24-59 Bulan; Kebijakan; Penanganan Stunting.